Activation of the δ‐opioid receptor promotes cutaneous wound healing by affecting keratinocyte intercellular adhesion and migration. (1st July 2014) - Bigliardi, P L; Neumann, C; Teo, Y L; Pant, A; Bigliardi‐Qi, M
<x xml:space="preserve">Abstract</x> Background and Purpose In addition to its analgesic functions, the peripheral opioid receptor system affects skin homeostasis by influencing cell differentiation, migration and adhesion; also, wound healing is altered in δ‐opioid receptor knockout mice (DOPr–/–). Hence, we investigated δ‐opioid receptor effects on the expression of several proteins of the desmosomal junction complex and on the migratory behaviour of keratinocytes. Experimental Approach Expression levels of desmosomal cadherins in wild‐type and DOPr–/– mice, and the morphology of intercellular adhesion in human keratinocytes were analysed by immunofluorescence. To investigate the δ‐opioid receptor activation pathway, protein expression was studied using Western blot and its effect on cellular migration determined by in vitro live cell migration recordings from human keratinocytes. Key Results Expression of the desmosomal cadherins, desmogleins 1 and 4, was up‐regulated in skin from DOPr–/– mice, and down‐regulated in δ‐opioid receptor‐overexpressing human keratinocytes. The localization of desmoplakin expression was rearranged from linear arrays emanating from cell borders to puncta in cell periphery, resulting in less stable intercellular adhesion. Migration and wound recovery were enhanced in human keratinocyte monolayers overexpressing δ‐opioid receptors in vitro. These δ‐opioid receptor effects were antagonized by specific PKCα/β inhibition indicating they were mediated through the PKC signalling pathway. Finally, cells overexpressing δ‐opioid receptors developed characteristically long but undirected protrusions containing filamentous actin and δ‐opioid receptors, indicating an enhanced migratory phenotype. Conclusion and Implications Opioid receptors affect intercellular adhesion and wound healing mechanisms, underlining the importance of a cutaneous neuroendocrine system in wound healing and skin homeostasis. Linked Articles This article is part of a themed section on Opioids: New Pathways to Functional Selectivity. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-2